2017
DOI: 10.5152/eurjrheum.2017.17026
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia has a high prevalence and impact in cardiac failure patients

Abstract: Objective: Chronic cardiac failure (CCF) shares several clinical features with fibromyalgia (FM), a syndrome of increased central sensitivity and musculoskeletal pain. FM frequently coexists with other chronic illness. Musculoskeletal pain is reported in patients with CCF; however, the prevalence and impact of FM in patients with CCF is not known. This research aims to assess the prevalence and effects of concurrent FM in patients with CCF and to identify other coexisting central sensitivity syndromes. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Cardiac failure is not commonly associated with chronic pain. Therefore, the report that FM occurred in 23% of persons with cardiac failure is of particular interest (Gist et al., ). In this study of 57 patients, 63% male and mean age 70 years, Gist and coauthors assessed FM using the 2011 ACR criteria, and overall health function was assessed with the short‐form (SF‐36).…”
Section: Resultsmentioning
confidence: 99%
“…Cardiac failure is not commonly associated with chronic pain. Therefore, the report that FM occurred in 23% of persons with cardiac failure is of particular interest (Gist et al., ). In this study of 57 patients, 63% male and mean age 70 years, Gist and coauthors assessed FM using the 2011 ACR criteria, and overall health function was assessed with the short‐form (SF‐36).…”
Section: Resultsmentioning
confidence: 99%
“…Autonomic dysregulation in FM sufferers reflects reduced adaptability and poor adjustment of the organism. Moreover, there is evidence that FM is associated with an increased risk of cardiovascular diseases; peculiarities in autonomic control may be involved in their pathogenesis (82,83). The involvement of depressive disorders in autonomic dysregulation underlines the importance of diagnosing and treating comorbid affective disorders in the management of FM.…”
Section: Original Articlementioning
confidence: 99%
“…However, one previous study reported that widespread pain was a risk factor for cardiovascular mortality (Tesarz et al, 2019). Another study investigated the several clinical features between HF and fibromyalgia and reported a prevalence of 22.8% of the studied cohort fulfilling both fibromyalgia diagnosis criteria and HF (Gist et al, 2017). This underscores the relationship between CWP and HF as relevant.…”
Section: Discussionmentioning
confidence: 99%
“…It is still not established if the pain is related to HF itself, high age, or the burden of comorbidity. Studies suggest that HF shares several clinical features with fibromyalgia, a syndrome characterized by chronic widespread pain (CWP), often attributed to increased central sensitivity (Gist et al, 2017). Central sensitization is a complex phenomenon with amplified signalling and enhanced sensitivity of nociceptive neurons within the central nervous system.…”
Section: Introductionmentioning
confidence: 99%